The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.1442-2050.2004.00375.x
|View full text |Cite
|
Sign up to set email alerts
|

Peptic esophageal stricture: a report from Argentina

Abstract: Peptic esophageal stricture (PES) is a major complication of gastroesophageal reflux disease. The aims of this paper were to determine the characteristics of these patients with regard to demography, morphology, functional status and results of therapy. The charts of the patients treated at our service who underwent esophageal dilatation for PES between 1971 and 1998 were reviewed. Statistical analyses were performed by means of chi2, Mann-Whitney and Student's t-tests. One hundred and thirty-five patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
(66 reference statements)
1
2
0
3
Order By: Relevance
“…The incidence of various symptoms were dysphagia 100%, regurgitation 45%, epigastric or substernal pain 35%, weight loss 25% and cough in 12% cases, which are comparable with study of Mazzadi SA [11] (2004) in which dysphagia (100%), regurgitation (40%) and epigastric pain (30%). Similar results were found in study of Ghoshal UC [6] (2004) with dysphagia (100%), regurgitation (48%), epigastric pain (17%), weight loss (26%) and pulmonary symptoms occurred in 18% cases.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The incidence of various symptoms were dysphagia 100%, regurgitation 45%, epigastric or substernal pain 35%, weight loss 25% and cough in 12% cases, which are comparable with study of Mazzadi SA [11] (2004) in which dysphagia (100%), regurgitation (40%) and epigastric pain (30%). Similar results were found in study of Ghoshal UC [6] (2004) with dysphagia (100%), regurgitation (48%), epigastric pain (17%), weight loss (26%) and pulmonary symptoms occurred in 18% cases.…”
Section: Discussionsupporting
confidence: 85%
“…The study of Mazzadi SA [11] (2004) on peptic stricture shows 97% of stricture present in lower one third of oesophagus. Chiu YC et al (2013) reported that, of the 18 patients with oesophageal stricture alone, 6 had orifices of strictures located in the upper third of the oesophagus, 6 in the middle third and 6 in the lower third.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…5,6 Wienbeck 7 (1989) juga melaporkan bahwa insiden peptic esophageal stricture meningkat di Jerman yaitu sekitar 10-20%. Mazzadi 8 di Argentina (2004) melaporkan insidennya sekitar 0.8% dari seluruh pasien GERD dengan rata-rata umur 44-77 tahun dan lebih sering pada laki-laki dibanding wanita dengan rasio 2,7:1.…”
Section: Definisiunclassified
“…Peptic esofageal sricture merupakan salah satu komplikasi jangka panjang dari GERD. 8 Sekitar 40-65% kasus GERD akan berkembang menjadi esofagitis erosif dan bila tidak diobati sekitar 4-23% esofagitis erosif ini akan berkembang menjadi striktur esofagus. 6 Faktor predisposisi terbentuknya striktur ini tidak begitu jelas, tapi beberapa studi menerangkan bahwa peptic esophageal stricture dapat terjadi pada refluks yang lama, adanya kelainan motilitas esofagus dan tekanan spingter bawah esofagus yang rendah.…”
Section: Patogenesisunclassified